Center-Related Variation in Hospitalization Cost for Patients Undergoing Percutaneous Left Atrial Appendage Occlusion - Shivaraj Patil, MD; Chaitanya Rojulpote, MD; Abhijit Bhattaru, BS; Avica Atri, MD; Krishna Vamsi Rojulpote, BS; Ola Khraisha, MD; Viha Atri, MD; William Frick, MD; Tarek Nafee, MD; Kishore Harjai, MD; Sumeet Mainigi, MD; Chien-Jung Lin, PhD, MD (Structural Heart)
Background: The commercial use of percutaneous left atrial appendage occlusion with the Watchman device is increasing in the United States. The purpose of this study was to evaluate center-related variation in total hospital costs for Watchman device implantation and identify factors associated with high hospital costs at a national level. Methods: All adults undergoing elective left atrial appendage occlusion with Watchman were identified in the 2016-2018 National Inpatient Database. Mixed models were used to evaluate the impact of center on total hospital costs, adjusting for patient and center characteristics and length of stay. Results: A total of 30,175 patients underwent Watchman device implantation at a median cost of $24,500 and demonstrated significant variability across admissions (interdecile range, $13,900-37,000). Nearly 13% of the variability in patient-level costs was related to the center performing the procedure rather than patient factors. Higher-volume centers had lower total costs and demonstrated lesser total cost variation. Centers with low procedural volume, occurrence of procedural complications, congestive heart failure, and length of stay were independent predictors of a high-cost hospitalization. Though complications were associated with increased expenditure, they did not explain the observed cost variation related to the center. Conclusions: A significant proportion of variation in total hospital cost was attributable to the center performing the procedure. Addressing variability of Watchman-related costs is necessary to achieve high-quality value-based care.